Basal Cell Nevus Syndrome. A Case Presentation - Ángel Luis Cruz Leiva; Blas Jorge González Manso; Orlando Sotolongo Terry (Medisur)
Basal Cell Nevus Syndrome is an infrequent entity of very low incidence according to reports in medical literature. It is characterized by considerable groups of alterations which are presented in the organism in a variable way, and with localized lesions in the maxillofacial area. A 61 year-old white male patient who lives in the urban area of Cienfuegos city is presented. He has family references of numerous physical deformities since he was born such as mental retardation, presence of moles since the first decade of his life and augmentation of the mandibular body volume. The diagnosis was keratocysts based on the clinical and radiological examinations as well as histopathological studies.